Răspuns :
2(x+1)^2=288
(x + 1)^2 = 288 : 2
(x + 1)^2 = 144
(x + 1)^2 = 12^2
Ix + 1I = 12
x + 1 = 12 x + 1 = - 12
x = 12 - 1 x = - 12 - 1
x = 11 x = -13
S = { - 13; 11}
(x + 1)^2 = 288 : 2
(x + 1)^2 = 144
(x + 1)^2 = 12^2
Ix + 1I = 12
x + 1 = 12 x + 1 = - 12
x = 12 - 1 x = - 12 - 1
x = 11 x = -13
S = { - 13; 11}
Salut,
Din enunț avem așa:
(x + 1)² = 288/2, sau (x + 1)² = 144, sau (x + 1)² = 12², sau
(x + 1)² -- 12² = 0 ⇒ (x + 1 -- 12)(x + 1 + 12) = 0.
x + 1 -- 12 = 0, deci x₁ = 11
x + 1 + 12 = 0, deci x₂ = --13.
Green eyes.
Din enunț avem așa:
(x + 1)² = 288/2, sau (x + 1)² = 144, sau (x + 1)² = 12², sau
(x + 1)² -- 12² = 0 ⇒ (x + 1 -- 12)(x + 1 + 12) = 0.
x + 1 -- 12 = 0, deci x₁ = 11
x + 1 + 12 = 0, deci x₂ = --13.
Green eyes.